우울, 불안, 치매 환자에 대한 매선 치료: 체계적 문헌 고찰 - 조준희; Jun-hee Cho; 박소현; So-hyeon Park; 김보경; Bo-kyung Kim; 임정화; Jung-hwa Lim (동의신경정신과학회지, 2024)
Objectives: This study aimed to systematically review thread-embedding treatment studies for depression, anxiety, and dementia and examine the effectiveness and safety of thread-embedding treatment. Methods: Ten domestic and international search databases were used for study selection, including CNKI, PubMed, CENTRAL, EMBASE, CINAHL, AMED, PsycArticles, RISS, OASIS, and KCI. We included studies that presented diagnostic or appropriate criteria for depression, anxiety, and dementia, and randomized control studies using thread-embedding therapy. We searched papers published until October 10, 2023. Results: Twenty-one studies were selected, of which 11 studies were conducted on depression, nine on dementia, and one on anxiety disorders. The most commonly used acupoint for depression was Gansu (BL18), whereas zusanli (ST36) and fenglong (ST40) were used for dementia. The most commonly used type of thread was 1-0 United States pharmacopeia (USP) and 1 cm for depression and 2-0 USP and 1 cm for dementia. The treatment period for most of the studies was once every 2 weeks and for 8 weeks. Among the included studies, 17 showed significant improvements in depression scales, such as Hamilton depression rating scale and Self rating depression scale, activities of daily living scales, and cognitive function scales, such as Hasegawa dementia scale and Mini-mental state examination. Six studies reported adverse events, and no studies reported significant adverse events. Two studies reported follow-ups. Conclusions: This study presents limited evidence for the effectiveness and safety of thread-embedding therapy for depression, anxiety, and dementia. Well-designed studies are needed to review the clinical efficacy and safety of thread-embedding therapy in the future.